Analisis Pengaruh Parameter Mesin Injection Molding Terdahap Diameter Housing Bearing Roller Conveyor Dengan Metode Response Surface - Achmad Syawariqul Anwar; Farizi Rachman; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
The roller conveyor bearing housing is one of the injection molded products from a plastic manufacturing company in Sidoarjo. During the production process, there is an issue concerning the mismatch of the bearing housing diameter with the specified tolerance limits, which also slows down the production process. This study aims to find the optimal process parameter combination on the injection molding machine used for producing roller conveyor bearing housings. The response variable observed is the bearing housing diameter. The material used is polypropylene. The varied parameters include injection pressure, injection time, and cooling time. Data analysis utilizes the response surface method with a Box-Behnken experimental design comprising 15 experiments and 3 replications. From the experimental results, the optimal combination for both the housing diameter and cycle time responses includes an injection pressure of 60 bar, injection time of 6 seconds, and cooling time of 30 seconds. Injection pressure contributes 8.4%, injection time contributes 38.43%, and cooling time contributes 14.85% to the overall response